Record of proceedings before the commissioners [electronic resource] : under the convention of February 8, 1896 at Montreal, June 16, 1897 and at Halifax, August 25 to September 29, 1897. - Bering Sea Claims Commission.; United States.; Great Britain. ([Washington? : G.P.O.?, 1897)
Vol. IV. Tables. Part of a CIHM set. For individual microfiches in this set see CIHM microfiches 14456-14461. At head of title: Behring Sea Claims Commission. Electronic reproduction. Mode of access: Internet. 44